The occurrence of the Atlantic species Pisodonophis semicinctus (Osteichthyes: Ophichthidae) in the Gulf of Antalya, Turkey - Gökoğlu, Mehmet; BiÃ§er, Erkan; Korun, Jale; Gökoğlu, Kemal; Teker, Serkan (Universitas Malikussaleh, 2020)
Fishermen caught a different eel species at night with hook on July 7, 2019 (36°48'59.21